Non-Pharmacological Interventions for Minimizing Physical Restraints Use in Intensive Care Units: An Umbrella Review - Cui, Nianqi; Yan, Xiaoli; Zhang, Yuping; Chen, Dandan; Zhang, Hui; Zheng, Qiong; Jin, Jingfen (Frontiers in Medicine, 2022)
Background: Many organizations have supported and advocated minimizing the use of physical restraints. However, the application of physical restraints to patients in intensive care is still common practice in many countries. Objective: To assess the effectiveness of various nonpharmacological interventions used to minimize physical restraint use in intensive care units and provide a supplement to the evidence summary for physical restraint guideline adaptation. Methods: Based on the umbrella review methodology, electronic databases were searched to identify systematic reviews published from January 2016 to December 2020. Two independent reviewers undertook the screening, data extraction, and quality appraisal. The methodological quality of each systematic review was evaluated with AMSTAR 2. The quality of evidence of each intervention was assessed according to the GRADE framework. The corrected covered area was calculated as a measure of overlap. Results: Forty-seven systematic reviews were included in the umbrella review, of which six were evaluated as high quality, five were of moderate quality, and the rest were of low or critically low quality. The corrected covered area range was from zero to 0.269. The included systematic reviews evaluated various types of nonpharmacological interventions for minimizing physical restraint use in intensive care units, which included multicomponent interventions involving education of healthcare professional, family engagement/support, specific consultations and communication, rehabilitation and mobilization (rehabilitation techniques, early mobilization, inspiratory muscle training), interventions related to reducing the duration of mechanical ventilation (weaning modes or protocols, ventilator bundle or cough augmentation techniques, early tracheostomy, high-flow nasal cannula), and management of specific symptoms (delirium, agitation, pain, and sleep disturbances). Conclusions: The number of systematic reviews related to physical restraint use was limited. Multicomponent interventions involving educating healthcare professional may be the most direct nonpharmacological intervention for minimizing the use of physical restraints in intensive care units. However, the quality of evidence was very-low, and conclusions should be taken with caution. Policy makers should consider incorporating nonpharmacological interventions related to family engagement/support, specific consultations and communication, rehabilitation and mobilization, interventions related to reducing the duration of mechanical ventilation, and management of specific symptoms as part of the physical restraint minimization bundle.